2006
DOI: 10.1073/pnas.0608175103
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence correlation spectroscopy shows that monomeric polyglutamine molecules form collapsed structures in aqueous solutions

Abstract: We have used fluorescence correlation spectroscopy measurements to quantify the hydrodynamic sizes of monomeric polyglutamine as a function of chain length (N) by measuring the scaling of translational diffusion times ( D) for the peptide series (Gly)-(Gln)N-Cys-Lys2 in aqueous solution. We find that D scales with N as oN and therefore ln( D) ‫؍‬ ln( o) ؉ ln(N). The values for and ln( o) are 0.32 ؎ 0.02 and 3.04 ؎ 0.08, respectively. Based on these observations, we conclude that water is a polymeric poor solve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

29
326
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 278 publications
(356 citation statements)
references
References 66 publications
29
326
1
Order By: Relevance
“…We measured the scaling of hydrodynamic sizes for monomeric polyglutamine in aqueous solution at ca. 25°C and showed that size scales as N 1/3 with chain length [62]. Interestingly, while the free energy of hydration for primary and secondary amides is highly favorable [63], we found that even short polyglutamine chains (ca.…”
Section: Applicability Of Polymer Physics Concepts To Study Of Aggregmentioning
confidence: 73%
“…We measured the scaling of hydrodynamic sizes for monomeric polyglutamine in aqueous solution at ca. 25°C and showed that size scales as N 1/3 with chain length [62]. Interestingly, while the free energy of hydration for primary and secondary amides is highly favorable [63], we found that even short polyglutamine chains (ca.…”
Section: Applicability Of Polymer Physics Concepts To Study Of Aggregmentioning
confidence: 73%
“…Therefore, within this diverse size-based population of oligomers could be discrete species of low concentration that contain specific conformations associated with toxicity. Support of this has been provided by in vitro polyQ studies (64,65), which suggest changes in conformation of the monomer and higher order species. In the future, separating size from conformationbased changes, perhaps through use of lifetime measurements, may allow oligomer populations to be further distinguished including an association with toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Aqueous milieus are poor solvents for polyglutamine (10). In poor solvents, there exists a threshold concentration for polymers, c = c s , known as the saturation concentration (11).…”
Section: Resultsmentioning
confidence: 99%